Social entrepreneurship - Nicholls, Alex (Oxford University Press, 2006)
Examines 'Social Entrepreneurship', a term that has come to be applied to the activities of grass-roots activists, NGOs, policy makers, international institutions, and corporations, amongst others, which address a range of social issues in innovative and creative ways. - ;'Social Entrepreneurship' is a term that has come to be applied to the activities of grass-roots activists, NGOs, policy makers, international